2016
DOI: 10.1097/j.pain.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Impaired conditioned pain modulation in youth with functional abdominal pain

Abstract: Functional abdominal pain (FAP) is associated with enhanced pain responsiveness. Although impaired conditioned pain modulation (CPM) characterizes adults with a variety of chronic pain conditions, relatively little is known about CPM in youth with FAP. The present study assessed CPM to evoked thermal pain in 140 youth (ages 10 to 17), 63 of whom had FAP and 77 of whom were healthy controls. Multilevel models demonstrated weaker CPM effects in FAP than healthy youth, as evident in slower within-person decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 56 publications
1
31
1
Order By: Relevance
“…Whilst these descriptive differences are generalisable across studies, different methods and time points have been used to compare the magnitude of CPM across groups. 4 , 16 , 36 , 40 , 41 Despite clear group increases in PPT after conditioning, there was a wide within-group variability in calculated percent CPM, as also seen in some previous evaluations in healthy adolescents 36 and adults. 42 This limited our ability to identify group differences in CPM magnitude.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Whilst these descriptive differences are generalisable across studies, different methods and time points have been used to compare the magnitude of CPM across groups. 4 , 16 , 36 , 40 , 41 Despite clear group increases in PPT after conditioning, there was a wide within-group variability in calculated percent CPM, as also seen in some previous evaluations in healthy adolescents 36 and adults. 42 This limited our ability to identify group differences in CPM magnitude.…”
Section: Discussionsupporting
confidence: 64%
“…Reduced inhibitory CPM 3 , 11 or a shift to facilitation has been reported in adults 38 , 40 and youth 41 with chronic pain. Here, there were no clear associations between current pain experience and the degree or directionality of CPM.…”
Section: Discussionmentioning
confidence: 92%
“…Firstly, this meta-analysis was confined to study conditioned pain modulation in IBS and thus extrapolation to other functional gastrointestinal disorders, where visceral pain is a defining feature, is uncertain although similar deficiencies in conditioned pain modulation have been reported in patients with functional dyspepsia and functional abdominal pain. 18,64 Secondly, within the literature to date, there is a female bias in the recruited subjects (88%), and therefore, generalisability to male patients is less certain. A previous meta-analysis reported that deficiencies in conditioned pain modulation in males are less than in females and may provide insights into the female preponderance in some types of IBS.…”
Section: Limitationsmentioning
confidence: 99%
“…While both Goffaux et al 8 and Williams et al 17 have proposed that pain inhibitory pathways are affected by frequent and early exposure to painful experiences, it is not yet conclusive if this exposure is predictive of the onset and severity of chronic pain later in life. However, the studies by Morris et al 14 and Rathleff et al 18 indicate that this effect is not solely limited to early life exposures and that the presence of MSK pain or functional abdominal pain may also alter the descending pain inhibitory pathways. A recent study by Holley et al did not identify the differences in inhibitory pain pathways among children with MSK pain compared to pain-free children.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the study by Williams et al 17 restricted the pain conditions to girls with IBS, the study by Goffaux et al 8 included only premature infants who stayed in the NICU as their pain condition of interest, and Morris et al restricted their inclusion criteria to functional abdominal pain. 14 In terms of MSK pain, Rathleff et al restricted their study condition to patellofemoral pain exclusively. 18 Restricting the pain conditions could eliminate possible CPM effect variability brought upon by the inclusion of various pain conditions.…”
Section: Discussionmentioning
confidence: 99%